MANAJEMEN STRATEGIK DI RUMAH SAKIT UNTUK PENINGKATAN KUALITAS PELAYANAN DI ERA DIGITAL: TINJAUAN LITERATUR - Famila Famila; Listiana Nur Fadillah; Purwadhi Purwadhi; Yani Restiani Widjaja (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2026)
Introduction: Hospitals in Indonesia face complex challenges in the digital era, demanding strategic management transformation to improve service quality and operational efficiency. This study aims to examine various aspects of hospital strategic management based on current literature. Methods: Through a systematic literature review approach of 12 open access scientific journal articles published between 2023-2025, a thematic analysis was conducted to identify patterns, trends, and gaps in the implementation of strategic management in Indonesian hospitals. Discussion: The principal findings highlight five key areas of strategic management: digital transformation, policy integration, operational efficiency, human resource development, and service quality improvement. Digital transformation is the primary catalyst for change, while innovation in human resource management and the implementation of Lean Hospital Management optimize operational efficiency. Integration of strategic policies has been proven to improve the quality of services and ultimately increase the competitiveness of hospitals. Conclusion: Strategic management is an essential foundation for hospitals navigating the complexities of the contemporary healthcare environment. Effective strategic management implementation has been shown to positively correlate with improved service quality, organizational competitiveness, and financial sustainability. Strategic hospital management requires a holistic approach that integrates technology, human resources, and operational policies to achieve high-quality and sustainable healthcare.